O setor público não-estatal: reconfiguração entre o Estado e a sociedade civil - Effgen, Deliane Paula (2010)
This research analysis the relationship between State and Civil Society after the nonstate- owned insertion was announced by Director Plan of State Machine Reform, in 1995. To show our objective, as the public, non-state-owned sector, we will discuss the administration reform of Brazilian's State, with regard to transferring to the non public sector, normal operations that were the State s obligation before. To comprehend the reasoning of the public non-state-owned sector, it is based on Bresser Pereira and Anthony Giddens; and, trys to identify the diffusion of a new relationship between State and Civil Society. We propose to demonstrate that the public non-state-owned sector is an experiment to support one social project, that wants to maintain the capitalist process development, from a new concept of Civil Society, and, therefore, from other intervention of social area. We intend to show evidence that the public non-state-owned sector defends it s necessity for the Civil Society to take out the rights conquered by social movement. To be a collaborator in the insertion of this social project by the active involvement of people who bet on democratic potential of social foundations and Non-State-Owned Organizations. This research pretends to get the attention of the public non-stated-owned sector, which is a representation of common people who want to transform the society, split in class, into one harmonic and integrated society that works to commons objectives. We try to present the objectives of Director Plan of State Machine Reform, with regard to the public non-state-owned sector, are related to third way presuppose, cause. Both want to broadcast a new relationship between State and Civil Society, with the Civil Society ceasing to fight for your benefits and rights, and to go work in a cooperating regime with State, ensuring the domination and the class exploration.